2014
DOI: 10.1245/s10434-014-3599-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Microscopic Disease with Hyperthermic Intraoperative Intraperitoneal Chemotherapy After Complete Cytoreduction Improves Disease-Free Survival in Patients with Stage IIIC/IV Ovarian Cancer

Abstract: The treatment of the microscopic disease following complete cytoreduction with HIPEC in patients with advanced ovarian cancer is effective and can prolong disease-free survival. This survival benefit was not seen in undifferentiated tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 34 publications
2
57
0
Order By: Relevance
“…[5]. Combined CRS and HIPEC against peritoneal carcinomatosis of colorectal, gynecological, and gastric origin appear to be superior to other treatment methods [7,8,16]. Solass et al developed PIPAC, which might be superior to HIPEC in theory.…”
Section: Discussionmentioning
confidence: 99%
“…[5]. Combined CRS and HIPEC against peritoneal carcinomatosis of colorectal, gynecological, and gastric origin appear to be superior to other treatment methods [7,8,16]. Solass et al developed PIPAC, which might be superior to HIPEC in theory.…”
Section: Discussionmentioning
confidence: 99%
“…1 Long-term OS has been reported to be less than 8 months in the most end-stage patients with OC. 25,37,41 The efficacy of HIPEC and CRS for treating PC originating from advanced OC is well established, and the survival obtained using HIPEC + CSR seems to be dramatically longer than that obtained with previously reported treatment approaches. 25,37,41 The present study indicates that HIPEC + CSR can be tailored according to the patient's general condition.…”
Section: Discussionmentioning
confidence: 99%
“…25,37,41 The efficacy of HIPEC and CRS for treating PC originating from advanced OC is well established, and the survival obtained using HIPEC + CSR seems to be dramatically longer than that obtained with previously reported treatment approaches. 25,37,41 The present study indicates that HIPEC + CSR can be tailored according to the patient's general condition. Furthermore, patients in poor general health condition who are initially ineligible for CRS can receive the benefits of dCRS several days after the administration of HIPEC, which improves their health condition, thereby potentially increasing long-term survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cascales-Campos et al 56 studied 87 patients, 52 of whom were treated with HIPEC (paclitaxel) and 35 were in the control group. The result showed that the 1 year disease-free survival was 81% vs 66,0% and 3 year disease-free survival was 63.0% vs 18.0% (P<0.05).…”
Section: Hyperthermic Intraperitoneal Chemotherapy Early Postoperatimentioning
confidence: 99%